1297. In-Vitro Antibacterial Activities of Cefiderocol (S-649266) Alone and With the Addition of Beta-Lactamase Inhibitors Against Multidrug-resistant Acinetobacter baumannii. (31st December 2020) - Abdul-Mutakabbir, Jacinda C; Nguyen, Logan; Maassen, Philip; Stamper, Kyle; Kebriaei, Razieh; Lev, Katherine; Morrisette, Taylor; Kaye, Keith S; Rybak, Michael J
Abstract: Background: Multidrug-resistant (MDR) infections caused by Acinetobacter baumannii continue to pose a serious public health threat. Cefiderocol (CFDC) is a new parental siderophore cephalosporin that has displayed potent activity against Gram-negative bacteria, more specifically non-fermenting Gram-negative bacilli, including A. baumannii . Although uncommon, elevated minimum inhibitory concentrations (MICs) to CFDC have been reported, when tested against A. baumannii isolates, in-vitro . The addition of beta-lactamase inhibitors has been shown to be successful in decreasing elevated CFDC MICs. The evaluation of sulbactam (SUL), tazobactam (TAZO), or clavulanic acid (CLAV) in addition to CFDC against A. baumannii isolates with elevated CFDC MICs, has yet to be reported. The objective of this study was to evaluate the activity of several beta-lactamase inhibitors in combination with CFDC against A. baumannii strains with high CFDC MICs. Methods: One hundred and fifty carbapenem-resistant A. baumannii strains were selected from the Anti-infective Research Laboratory. MIC susceptibility testing was performed for all of the strains via broth microdilution (BMD). Seven strains that exhibited elevated CFDC MICs, 16-32 mg/L, were assessed via BMD, with the addition of the following beta-lactamase inhibitors: TAZO, SUL, AVI, and CLAV to CFDC. All in-vitro testing for CFDC was completed with the use of iron-depleted cation-adjusted Mueller-Hinton broth to ensure the induction of bacterial iron transporters per manufacturer standards. Results: A decline in elevated CFDC MIC values was observed in six of the seven A. baumannii strains, with the addition of each beta-lactamase inhibitor. AVI showed the most potent activity when added to CFDC, with an average 28- fold reduction in MIC values observed. SUL and CLAV produced similar fold reductions in the MIC values with an average 20-fold reduction observed with the addition of either agent to FDC. The addition of TAZO to CFDC also presented with a decline in MIC values, with an average 7-fold-reduction observed. Cefiderocol (CFDC) strains with MICs of 16-32 mg/l plus Beta-Lactamase Inhibitors Conclusion: The addition of several beta-lactamase inhibitors to CFDC has shown promise in decreasing elevated CFDC MICs. Further research is warranted to determine the role of BLIs on CFDC activity. Disclosures: Michael J. Rybak, PharmD, MPH, PhD, Paratek (Grant/Research Support)